SPATIAL AND TEMPORAL B-VALUE ANALYSIS OF THE YOGYAKARTA REGION USING EARTHQUAKE DATA 1960 â€“ 2024 - R, Sari Rahayu; Madrinovella, Iktri (JGE (Jurnal Geofisika Eksplorasi), 2024)
Yogyakarta is one of the areas in Indonesia with a high risk of earthquakes due to its proximity to the subduction zone of the Indo-Australian Plate and Eurasian Plate and the presence of active fault activity, namely the Opak fault, which generates shallow earthquakes. A total of 13 destructive earthquakes were recorded in Yogyakarta and surrounding areas from 1840 to 2023, with the most destructive earthquake occurring in 2006 in Bantul. A total of 417 earthquakes were felt in the Yogyakarta area between May 2006 and March 2016. The high earthquake activity after the 26 May 2006 earthquake indicates a stress field on the active fault segment that has not been fully released.Â  This study aims to analyze the seismotectonic parameter b-value spatially and temporally to determine the accumulation of tectonic stress in Yogyakarta. The method used is a frequency-magnitude distribution with Gutenberg-Richter relation and Maximum Likelihood approach. Earthquake data were obtained from ISC and BMKG catalogs, with a total of 205 events. The results show that spatially, the b-value of the Yogyakarta region is generally low with a range of values of 0.35 - 0.75 using a grid of 1.5 x 1.5 km and a radius of 15 km with low values around the Opak fault and Ngalang Fault, meaning that the area still holds a high accumulation of stress energy and has the potential for large earthquakes to occur again in the future. Temporal analysis of the b-value shows a tendency for the b-value to decrease before a large earthquake and increase afterwards, reflecting the accumulation and release of stress in the rock.